2019
DOI: 10.1016/j.jvs.2018.05.229
|View full text |Cite
|
Sign up to set email alerts
|

The impact of chronic kidney disease on lower extremity bypass outcomes in patients with critical limb ischemia

Abstract: CKD is a significant predictor of perioperative morbidity after lower extremity bypass. Patients with severe CKD have worse postoperative outcomes without increased mortality. Those on HD have worse survival and postoperative outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 22 publications
1
20
0
Order By: Relevance
“…Twenty-one studies defined normal kidney function by serum creatinine. Non-emergent cardiac surgery was the most commonly reported type of surgery (15 studies, 31%), [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] followed by general surgery (12 studies, 25%), [4,[35][36][37][38][39][40][41][42][43][44][45] vascular surgery (9 studies, 18%), [41,[46][47][48][49][50][51][52][53] orthopaedic surgery (9 studies,18%) [54][55][56][57][58][59][60][61] and urologic/gynaecologic surgery (4 studies, 8%)(62-65). Twenty-two of the 49 studies assessed a single surgical procedure, [24-27, 29, 31-34, 39, 41, PLOS ONE https://doi.org/10.1371/journal.pone.0234402.g001 Thirty six studies did not report dialysis modality, eleven studies specifically examined haemodialysis patients only,…”
Section: Description Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-one studies defined normal kidney function by serum creatinine. Non-emergent cardiac surgery was the most commonly reported type of surgery (15 studies, 31%), [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] followed by general surgery (12 studies, 25%), [4,[35][36][37][38][39][40][41][42][43][44][45] vascular surgery (9 studies, 18%), [41,[46][47][48][49][50][51][52][53] orthopaedic surgery (9 studies,18%) [54][55][56][57][58][59][60][61] and urologic/gynaecologic surgery (4 studies, 8%)(62-65). Twenty-two of the 49 studies assessed a single surgical procedure, [24-27, 29, 31-34, 39, 41, PLOS ONE https://doi.org/10.1371/journal.pone.0234402.g001 Thirty six studies did not report dialysis modality, eleven studies specifically examined haemodialysis patients only,…”
Section: Description Of Included Studiesmentioning
confidence: 99%
“…[20, 39, 56, 62] Thirty four studies were published after 2010. [4, 20, 22, 29-31, 34-38, 40, 41, 43-46, 50-61, 63-67] All 49 studies reported age and gender, but comorbidities were less consistently described, with 37 (76%) studies reporting the prevalence of diabetes mellitus, [4, 20-25, 27, 28, 30-37, 40, 41, 43, 45-56, 58, 61, 65-67] 31 (63%) reporting ischaemic heart disease(IHD), [4, 20-28, 30, 32, 34-37, 41, 43, 45, 47-50, 52-56, 61, 65, 67] 21 (43%) reporting smoking status,[23, 25, 30, 32-36, 40-42, 46-49, 51, 53, 67] and 15 studies (31%) reporting all three comorbidities [32,35,36,45,47,49,52,61,65,[68][69][70][71][72][73].…”
mentioning
confidence: 99%
“…18,23 It should be noted that postoperative acute kidney injury (AKI) may occur in up to 12% of CKD patients treated with BG, while renal impairment is associated with increased postoperative morbidity. 24,25 The hypovolemic state of the patient, acute decompensated heart failure, or even mechanical ventilation during a surgical procedure can all together contribute to the development of AKI. Thus, AKI in patients with CKD can be a result of complex organ interactions regardless of the applied treatment option and does not necessary correlate with the administration of contrast agents.…”
Section: Discussionmentioning
confidence: 99%
“…A surgical revascularization procedure in patients with CKD can be technically demanding because of the tibial distribution of the disease and the excessive vessel calcification, leading to increased rates of graft failure. 25 Moreover, if a saphenous vein is absent or inadequate, most surgeons are reluctant to use an arm vein conduit, as this could be later used for an arteriovenous access. Furthermore, the malnutrition of the patient might negatively affect the wound healing process.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, our sample composed of patients younger than usual dialysis patients since atherosclerotic stenosis of lower extremity arteries, common in chronic renal failure and more common among those with advanced age, resulted in the exclusion of these patients. 20,21 Hence, even if there was a negative effect of atherosclerosis on flow redirection, it should have been at a minimum level. Only 27% of 11 AVFs that we created were functional and those patients had experienced the aforementioned advantages.…”
Section: Discussionmentioning
confidence: 99%